Indigence to independence : the development of social policy in New Zealand for people with learning disabilities : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University - Thomson, Janet Beattie (Massey University, 1995)
This study traces the development of social policy in New Zealand for people with learning disabilities. The study examines the social influences and the outcomes of past social policies which have shaped the development of an increasingly explicit social policy for disabled people. Integral to this analysis is a consideration of the impact of these policies upon the family. This study suggests that social policy, in establishing services which have moved people with learning disabilities progressively towards independence, has required a concomitant role of the family that has increasingly involved them in the lives of their dependants. Social policy for people whose learning capacity is impaired reflects society's movement towards an understanding of the condition as a "learning disability"1. 1 The terms that recognise an impairment in intellectual functioning are subject to ongoing debate amongst the disabled community. Since this thesis was commenced, the term "intellectual disability" has returned to use alongside "learning disability". The term "intellectual disability" reflects disabled people's intent to have their disability recognised as a valid part of self. The term "learning disability" arises out of the notion of difference, which includes such 'otherness' as impaired intellectual functioning, within its continuum. The term "learning difficulty" extends this continuum further. The forms which recognise an impairment in Intellectual functioning have moved to increasingly positive modes, removing the stigma associated with other labels such as "mentally retarded". The study examines the changes in societal perceptions of learning disabled people which been fundamental in the construction of social policy, partnering changes in philosophies of care that in turn have shaped the nature of service delivery. Notions of deviancy. sickness, difference and partnership underpinned the development of social policy, as it related to people with learning disabilities, from the 1840s. Services to people with learning disabilities have been delivered by both the State and the voluntary sector. The study contrasts the role of the State as a major service provider through the health, education and welfare sectors with the role established by voluntary agencies. A discussion of the development of service provision to people with learning disabilities provides an understanding of the changing relationship between the State and voluntary sectors. Ideologies of 'welfare' underpinned the provision of services through the period of this study and were themselves influenced by the wider political and economic environment. Laissez-faire ideologies in the settlement period of the nineteenth century, fabian socialism in the 1930s and libertarian ideologies in the 1980s are discussed as they relate to the formation of social policy for people with learning disabilities. The State's changing role in providing for the welfare needs of its citizens, including those with learning disabilities, is discussed against this background. The outcomes of past policies have been a major influence in the development of current social policy. Current policies are likely in their own turn to influence the nature of future social policy and services to those with learning disabilities. Some consideration is given to the implications they might hold for families who have dependants with learning disabilities, and for people with learning disabilities themselves.
Keywords: People with mental disabilities; Care; Institutional care; Public opinion; New Zealand